2005
DOI: 10.1115/1.2073671
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Nanoindentation Technique to Measure Bone Tissue Lamellae Properties

Abstract: Measuring the microscopic mechanical properties of bone tissue is important in support of understanding the etiology and pathogenesis of many bone diseases. Knowledge about these properties provides a context for estimating the local mechanical environment of bone related cells thait coordinate the adaptation to loads experienced at the whole organ level. The objective of this study was to determine the effects of experimental testing parameters on nanoindentation measures of lamellar-level bone mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
130
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 49 publications
23
130
0
2
Order By: Relevance
“…As noted in the literature Hoffler et al, 2005), there are differences in the measured modulus and hardness values when testing hydrated vs. dry specimens, thus the measured values presented here would likely decrease if tested under hydrated conditions. It is not clear, however, whether or not the maximum high-load penetration depths encountered in this study (on the order of 3000 nm, 3-5 times larger than in Rho and Hoffler, respectively) would still result in significantly different hydrated vs. dry results; and whether or not the trends observed between hydrated and dry specimens would be similar to those observed in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As noted in the literature Hoffler et al, 2005), there are differences in the measured modulus and hardness values when testing hydrated vs. dry specimens, thus the measured values presented here would likely decrease if tested under hydrated conditions. It is not clear, however, whether or not the maximum high-load penetration depths encountered in this study (on the order of 3000 nm, 3-5 times larger than in Rho and Hoffler, respectively) would still result in significantly different hydrated vs. dry results; and whether or not the trends observed between hydrated and dry specimens would be similar to those observed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…An increasing number of measurements of hardness and Young's modulus of bone have been made using different nano-instruments (Turner et al, 1999;Hengsberger et al, 2003;Rho and Pharr, 1999;Hoffler et al, 2005;Ashman and Rho, 1988;Fan et al, 2002;Garner et al, 2000;Fan and Rho, 2003). However, testing conditions have not been uniform.…”
Section: Introductionmentioning
confidence: 99%
“…The unloading segment of the load-displacement curve was analyzed using a mathematical solution derived by Oliver and Pharr [8]. Two sets of elastic modulus and hardness were calculated for each specimen using the CSM method (E CSM and H CSM ) from the loading segment [8,17] and the Oliver-Pharr method (E O-P and H O-P ) from the unloading segment [1,6,8,17], respectively. E CSM and H CSM were averaged from 200 to 500 nm in the modulus-displacement curve and the hardness-displacement curve, respectively, because the initial calculations of modulus and hardness were unstable.…”
Section: Nanoindentationmentioning
confidence: 99%
“…Nanoindentation has been widely used to study tissue mechanical properties (elastic modulus and hardness) of both cortical [1][2][3] and cancellous bone [4][5][6][7][8]. The method and equations used to calculate bone tissue modulus and hardness in these studies were based on the assumption that the bone was linearly elastic and, therefore, the material properties remained constant independent of the indentation depth [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the bone elastic modulus obtained from NI was generally lower under wet conditions than in the dry state [36,[38][39][40]. However, in the previous studies, the samples were first dried, followed by rehydration, after at least 24 hours of immersion in various solutions, such as 3.7% formaldehyde, 4% paraformaldehyde, Ringer's solution, and ethanol.…”
Section: Discussionmentioning
confidence: 99%